A rare complication of ventriculoperitoneal shunt: Pleural effusion without intrathoracic ventriculoperitoneal shunt catheter - Hilmani, Said (Surg Neurol Int, 2020)
BACKGROUND: Symptomatic pleural effusion following ventriculoperitoneal shunt (VPS) insertion is very rare and poorly understood in the literature in contrary to other mechanical complications. CASE DESCRIPTION: We report a case of 15 month-year-old girl who had VP shunt for congenital hydrocephalus. Twelve months after surgery, she was diagnosed with massive hydrothorax. Chest X-ray and thoracoabdominal CT scan confirmed the right pleurisy and showed the tip of the peritoneal catheter in the general peritoneal cavity. We made thoracic drainage of the transudative pleural effusion. When we released the chest tube, 24 h after, the girl showed a respiratory distress again and the effusion resumed at the X-ray control. Her symptoms abated after the realization of a ventriculoatrial shunt “VAS.” Repeat chest X-ray confirmed the resolution of the hydrothorax. CONCLUSION: Despite the not yet well-understood mechanism of this rare and important VPS complication, management is simple based on X-ray confirmation, thoracentesis with biological analysis, and catheter replacement, especially in atrium “VAS.”